Moral Error Theory, Entailment and Presupposition - Kalf, Wouter Floris (Ethical theory and moral practice, 2013)
According to moral error theory, moral discourse is error-ridden. Establishing error theory requires establishing two claims. These are that moral discourse carries a non-negotiable commitment to there being a moral reality and that there is no such reality. This paper concerns the first and so-called non-negotiable commitment claim. It starts by identifying the two existing argumentative strategies for settling that claim. The standard strategy is to argue for a relation of conceptual entailment between the moral statements that comprise moral discourse and the statement that there is a moral reality. The non-standard strategy is to argue for a presupposition relation instead. Error theorists have so far failed to consider a third strategy, which uses a general entailment relation that doesn’t require intricate relations between concepts. The paper argues that both entailment claims struggle to meet a new explanatory challenge and that since the presupposition option doesn’t we have prima facie reason to prefer it over the entailment options. The paper then argues that suitably amending the entailment claims enables them to meet this challenge. With all three options back on the table the paper closes by arguing that error theorists should consider developing the currently unrecognised, non-conceptual entailment claim.